Effects of Saponin and L-Carnitine on the Performance and Reproductive Fitness of Male Broiler - Miah, M.Y.; Rahman, M.S.; Islam, M.K.; Monir, M.M. (International Journal of Poultry Science, 2004)
A factorial bioassay was made to evaluate 4 different levels of exogenous saponin (S); 0 mg (So), 25 mg (S1), 50 mg (S2) and 75 mg (S3) per kg and also a combination (SC) of 50 mg saponin plus 50 mg L-carnitine (S4) per kg maize-soybean meal based basal diet during the late autumn. In all, 5 experimental diets being iso-nutritive (as per NRC, 1994 recommendation) but for variable in presence and contents of saponin and L-carnitine were prepared. 8-day old male broiler chicks (n=150, Starboro) were distributed randomly into 15 groups of 10 chicks in each housed in separate pen of littered floor. Three such groups received each of 5 test diets ad libitum as mash up to 8 weeks of age. The plenty of water was made available to all chicks during the experimental period. It was found that S2 diet significantly improved body weight gain (BWG) during growing (8 days to 3 weeks) period when compared with S0, S1, S3 and S4. Dietary S and SC had no significant (p>0.05) effect separately and jointly on feed efficiency, protein efficiency and performance index. But S3 and S4 diets reduced abdominal fat significantly (p